2020
DOI: 10.1007/s12541-020-00445-2
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Smart Factory for SMEs: Concept, Application and Perspective

Abstract: In the manufacturing industry, the smart factory is considered the final stage of the Fourth Industrial Revolution. Manufacturing companies are pursuing breakthroughs by introducing various advanced technologies to ensure their competitiveness. However, it is difficult for small and medium-sized enterprises (SMEs) to adopt smart-factory technologies, owing to financial and technical burdens. This paper proposes a smart factory that can be applied technically and strategically to the introduction of a smart fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 50 publications
0
21
0
1
Order By: Relevance
“…Rauch and Vickery (2020) investigated that self-control is the key requirement and crucial for SM. Jung et al (2021) identified that productivity is the key performance that needs to be more focused on implementing SM. Dynamic scheduling is the significant critical performance measure of SM (Yang et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Rauch and Vickery (2020) investigated that self-control is the key requirement and crucial for SM. Jung et al (2021) identified that productivity is the key performance that needs to be more focused on implementing SM. Dynamic scheduling is the significant critical performance measure of SM (Yang et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…, 2020a; Frank et al. , 2019a), the adoption of Industry 4.0 technologies by manufacturing industries (Zheng et al , 2019) could follow three main directions strictly related to the main improvements linked to the concept of smart factory (Jung et al , 2021), that technolgies allow to ahcieve: (1) efficiency and productivity, (2) flexibility and customization and (3) data processing.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Scholars recently have showed that such technologies could be grouped into main clusters based on the use and the impacts of the different technologies on business and manufacturing processes (Zheng et al, 2021). Although different clusters emerged (Culot et al, 2020a;Frank et al, 2019a), the adoption of Industry 4.0 technologies by manufacturing industries (Zheng et al, 2019) could follow three main directions strictly related to the main improvements linked to the concept of smart factory (Jung et al, 2021), that technolgies allow to ahcieve: (1) efficiency and productivity, (2) flexibility and customization and (3) data processing.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we look at the maturity level of smart fashion factories. Most of the fashion industry belongs to small and medium-sized enterprises (SMEs), and some studies confirm maturity in some SMEs [23,24]. This suggests future directions for improvement after examining the low maturity level of smart fashion factories compared to other industries.…”
Section: Maturity Of Smart Fashion Factorymentioning
confidence: 99%